A method to break charge transfer complex of polyimide: A study on solution behavior. Issue 1 (2nd May 2012) - Ke, Fuyou; Song, Naiheng; Liang, Dehai; Xu, Hongyao
Abstract Charge transfer complex strongly affects the optical transparency of polyimide film. Here, solution behavior of a polyimide derived from 3, 3′, 4, 4′ biphenyltetracarboxylic dianhydride and 1, 4‐bis(3‐aminopropyl)piperazine in acetic acid, chloroform, and their mixed solvents is investigated in detail by light scattering. It is found that the polyimide existed as single chains in acetic acid owing to the acid‐base interaction. However, association is observed in chloroform solution because of the charge transfer complex and enhanced by increasing the solution concentration. To break the charge transfer interaction and clear the association, only a small amount of acetic acid is required to add into the chloroform solution owing to the protonation of the diamine groups, confirmed by the zeta potential measurements. Simultaneously, the associates disappear quickly after addition of acetic acid. This study will provide a novel method for preparation of high optical transparent polyimide film by simply tuning the solvent. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012